About the Relationship Between Quantum Mechanics and Finances - Quispe Gallegos, Luis Enrique (2023)
The present article has as a goal to show an alternative way for deriving the Black-Scholes equation using the Schrödinger equation of quantum mechanics, taking into account that both of these partial differential equations are quite similar.